A new species of Eufriesea Cockerell (Hymenoptera, Apidae, Euglossina) from northeastern Brazil - Faria,Luiz R. R. (2011)
A new species of Eufriesea Cockerell (Hymenoptera, Apidae) from northeastern Brazil. Eufriesea pyrrhopyga sp. nov. a short-tongued Eufriesea is described as a new species. It can be easily recognized for its predominantly violet lower frons and thorax, violet tergum 1 contrasting with the strong reddish coloration on the lateral portions of terga 2 to 4 and on entire terga 5 and 6, and head pubescence with contrasting colors, white on the lower two-thirds of the face and black on upper frons and vertex. This new species, collected in Recife (Pernambuco, Brazil), apparently is restricted to the Pernambuco endemic center, and seems to be highly endangered.